Pengaruh Penempatan dan Pelatihan Kerja Terhadap Kinerja Pegawai di Dinas Pendidikan Provinsi Sumatera Barat - Dilla Puspita Hadi; Marwan Marwan (Universitas Negeri Padang, 2019)
His study was conducted to determine (1) the effect of placement and job training on employee performance, (2) the effect of placement on employee performance, (3) the effect of job training on employee performance. This research is descriptive associative. The population in this study were employees of the Education Office of West Sumatra Province with 182 employees. The total sample is determined using the Slovin formula and cluster sampling. From this pattern, 125 employees were obtained as research samples. The data collection technique used in this study was a questionnaire. The validity test instrument uses Collected Item-Total Colleration and for reliability testing using alpha coefficient formula. Prerequisite tests were carried out by normality test, heterocedasticity test, and multicollinearity test. The technique used to analyze data is multiple regression analysis. Based on this study, it was found that (1) Job Placement and Training had a positive and significant effect on the performance of West Sumatra Provincial Education Office employees (2) Placement had a positive influence and significantly affected the performance of West Sumatra Provincial Education Office employees (3) Job Training had a positive effect and significant to the performance of employees of the Education Office of West Sumatra Province. Keyword: placement, job training, employee performance